Personal Innovation: The Role of Leadership dan Motivation to Learn - Yunianto Agung Nugroho; Jainuri Jainuri; Vanessa Stefanny; Hatoli Waruwu; Siti Mariyanah (Universitas Muhammadiyah Enrekang, 2022)
This study aimed to investigate the influence of transformational leadership on the innovative work behavior of employees and the mediating role of learning motivation in the relationship between transformational leadership and innovative work behavior. The questionnaire, designed as a self-reported survey, was distributed to regular employees of a manufacturing company in the automotive sector. Data was collected from 203 employees. The hypothesis is tested using structural equation modeling. Data processing uses the SEM method with SmartPLS 3.0 software. The findings indicate that transformational leadership has a positive impact on employees' innovative work behavior and motivation to learn to mediate the transformational leadership-innovative work behavior relationship. This study contributes to the existing literature by providing empirical evidence about the effect of transformational leadership on employee innovative work behavior and the impact of innovative work behavior variables. The implication is that organizations must pay attention to creating a climate that supports innovation and encourages individuals to learn new knowledge and skills, and provides employees with opportunities to use the knowledge and skills they have acquired.